SALDO's morphology - Språkbanken Text (University of Gothenburg, 2024)
Semantic and morphological lexicon for language technology

Semantiskt och morfologiskt lexikon för språkteknologi
SALDOs morfologi
Keywords: Language Technology (Computational Linguistics); lexicon; Natural Language Processing; Språkbehandling och datorlingvistik